Constructing Emotional Complexity: A Comparative Semiotic Analysis Of Childhood And Adolescent Emotions In Pixar’s Inside Out Posters - Iin Afriyanti; Rohmah Nur Fajriyati; Nurmaya Khoerunnisa; Annisa Nuansa Indah; Angga Krisaccani; Mayang Pipit (English Education Study Program FKIP Universitas Alwashliyah Medan, 2026)
Mental health and emotional development have received increasing attention across various fields, including popular media, which plays a significant role in shaping public understanding of human emotional experiences. The studies examining the visual construction of emotional complexity in film posters, particularly those comparing different developmental stages within the same film franchise, remain limited. This study aims to analyze how emotional complexity is represented in the official posters of Inside Out (2015) and Inside Out 2 (2024) using Roland Barthes’ semiotic framework. Employing a qualitative approach, the study analyzes two official posters through three levels of meaning: denotation, connotation, and myth. The findings reveal a transformation in emotional representation, marked by a shift from Joy to Anxiety as the central visual focus. While the Inside Out poster constructs childhood as an optimistic and emotionally balanced stage dominated by basic emotions, the Inside Out 2 poster portrays adolescence as a more complex phase characterized by emotional diversity, uncertainty, identity negotiation, and psychological complexity. This shift reflects broader cultural constructions of emotional development and mental health. The findings extend the application of Barthesian semiotics in visual culture studies and demonstrate that emotional meanings are constructed from the promotional stage through film posters, which function as cultural texts shaping public understanding of human emotional development.